2019
DOI: 10.21273/hortsci13674-18
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Huanglongbing and Foliar Applications of Copper on Growth and Nutrient Acquisition of Citrus sinensis cv. Valencia

Abstract: The following study was conducted in 2016 and 2017 to determine the impact of frequent foliar copper (Cu) applications on Huanglongbing (HLB)-affected Citrus sinensis cv. Valencia orange. The experiment was conducted in a psyllid-free greenhouse with HLB-positive and non-HLB control trees grown in an Immokalee fine sand soil. The trees were well-maintained to promote health. Cu was applied to the foliage at 0x, 0.5x, 1x, and 2x the commercially recommended rates, which were 0, 46, 92, and 184 mM, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 24 publications
2
23
1
Order By: Relevance
“…The first paper in this series demonstrated that the pH of the soil in which HLB-affected trees grew was lowered compared with the soil in which non-HLB controls were grown. Reduced soil pH solubilized soil Cu and promoted higher uptake in HLB-affected trees than the non-HLB control [13]. The low pH-induced solubilization of soil cations has a reason for nutrient uptake and improved fertilization management of commercial citrus groves with HLB.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The first paper in this series demonstrated that the pH of the soil in which HLB-affected trees grew was lowered compared with the soil in which non-HLB controls were grown. Reduced soil pH solubilized soil Cu and promoted higher uptake in HLB-affected trees than the non-HLB control [13]. The low pH-induced solubilization of soil cations has a reason for nutrient uptake and improved fertilization management of commercial citrus groves with HLB.…”
Section: Resultsmentioning
confidence: 99%
“…This approach removed bias in tree size across all treatments when the experiment was initiated. Total leaf area was determined by counting leaves and measuring 10 leaves per tree, as described by Ebel et al [13].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations